Analysis of Motor Vehicle Tax, Motor Vehicle Title Transfer Tax, and Motor Vehicle Fuel Tax in 2018 - 2022 on Local Revenue in DKI Jakarta Province - Herawati, Putri; Nasrullah, Nasrullah; Rosida, Siti Ayu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to analyze the effectiveness and contribution of motor vehicle taxes, motor vehicle title transfer fees, motor vehicle fuel taxes to DKI Jakarta's PAD in 2018-2022. This research uses a qualitative descriptive method with secondary data obtained from local government financial reports via the official website of the Jakarta Information and Documentation Service. The data analysis technique used is the effectiveness analysis method with the effectiveness ratio and contribution analysis method. The results of this study show that there is effectiveness in the realization of motor vehicle tax with a very good level of effectiveness with an average of 100.81% and motor vehicle transfer fee tax with an average of 102.16% and motor vehicle fuel tax with an average of an average of 103.89% has a very good effectiveness level with a percentage that fluctuates from year to year. Motor vehicle tax contributes quite a bit and motor vehicle transfer fee tax has a low level of contribution to the PAD of DKI Jakarta Province, then motor vehicle fuel tax has a very low level of contribution to PAD of DKI Jakarta Province.